2013
DOI: 10.1088/0022-3727/46/13/135205
|View full text |Cite
|
Sign up to set email alerts
|

Glow corona generation and streamer inception at the tip of grounded objects during thunderstorms: revisited

Abstract: The initiation of streamers prior to a lightning strike can be reportedly inhibited by glow corona discharges generated from tall objects. In contrast to previous studies based on a simplified one-dimensional model of glow corona, a two-dimensional evaluation of the corona ion drift from tall objects is used here to analyse this effect quantitatively. Proper estimates for the corona space charge distribution generated during both the charging process of a thundercloud and the descent of the downward stepped le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 25 publications
2
39
0
Order By: Relevance
“…, , exp 0.01 0.02 (9) where is the radius of inner conductor and , are coordinates (unit in cm). The maximum density 10 cm is assumed as a reasonable value of nature background ionization caused by radioactivity and cosmic rays [38].…”
Section: Initial Condition and Applied Voltagementioning
confidence: 99%
See 2 more Smart Citations
“…, , exp 0.01 0.02 (9) where is the radius of inner conductor and , are coordinates (unit in cm). The maximum density 10 cm is assumed as a reasonable value of nature background ionization caused by radioactivity and cosmic rays [38].…”
Section: Initial Condition and Applied Voltagementioning
confidence: 99%
“…Since thunderclouds are mostly negatively charged, high electric fields are often induced on grounded tall objects, producing positive glow corona discharges. It has been suggested that the transition from glow corona to streamers is vital when investigating the initiation of upward lightning [5][6][7][8][9][10]. For the above-mentioned reasons, it is of great interest to evaluate the conditions required for the transition from stable glow corona to streamers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they assumed that the wind blew radially from the rod tip, which is of no practical significance. By using a 2D symmetrical model, Becerra [17] argued that the simulated results of Bazelyan et al [13] overestimated the influence of the corona discharge. Zou et al [15] have developed a 2D time-dependent model and found that the corona current increases almost linearly with the horizontal wind speed, but the effect of vertical wind on the corona current was not considered.…”
Section: Introductionmentioning
confidence: 99%
“…Although in most of the current numerical simulations [9,10,13,16,17], the corona discharge on the grounded objects is seen as symmetric. In practice, corona discharges on a grounded object during a thunderstorm can hardly avoid the presence of the wind.…”
Section: Introduction Of the Time-dependent Numerical Model Ofmentioning
confidence: 99%